Anti-social behaviour in Britain: Victorian and contemporary perspectives - Pickard, Sarah (Palgrave Macmillan, 2014)
Machine generated contents note: -- Introduction -- PART I: ANTI-SOCIAL BEHAVIOUR, THE URBAN ENVIRONMENT AND PUBLIC SPACES -- 1. A Less than Polite People? Incivility, Ruffianism and Anti-Social Behaviour in Urban England, 1830-1900; Neil Davie -- 2. Anti-social City: Science and Crime in late-Victorian Britain; Trevor Harris -- 3. Greater Expectations: Intolerance and Control of Public Space, Anti-social Behaviour in the Nineteenth and Twenty-first Centuries; Craig Johnstone -- 4. Anti-social Behaviour and 'Civilizing' Regulation in the British City: Comparing Victorian and Contemporary Eras; John Flint and Ryan Powell -- 5. From Scurrilous Periodical to the Public Platform. Policing Blasphemers and Anti-social Behaviour: Constructing the Public Peace Then and Now; David Nash -- 6. Anarchists, Authorities and the Battle for Public Space, 1880-1914: Recasting Political Protest as Anti-social Behaviour; Constance Bantman -- 7. Keep Them Kettled! Student Protests, Policing and Anti-social Behaviour; Sarah Pickard -- 8. Anti-social Behaviour and the London 'Riots': Social Meaning-making of the Anti-social; Christian Morgner -- 9. The Aesthetics of Anti-social Behaviour; Andrew Millie -- PART II: ANTI-SOCIAL BEHAVIOUR, THE VULNERABLE AND THE MARGINALIZED -- 10. Addressing Juvenile Anti-social Behaviour in Victorian England: Mary Carpenter and the Reformatory Schools; Aure;lie Baudry -- 11. Truancy and Anti-social Behaviour in England in the late Victorian Era and under New Labour; Anne Beauvallet -- 12. The Politics of 'Anti-Social' Behaviour within the 'Troubled Families' Programme; Sue Bond-Taylor -- 13. Anti-Social Behaviour Among Homeless People: Assumptions or Reality?; Jamie Harding and Adele Irving -- 14. Is Nomadism the 'Problem'? The Social Construction of Gypsies and Travellers as Perpetrators of 'Anti-social' Behaviour in Britain; Colin Clark and Becky Taylor -- 15.The Complexities, Contradictions and Consequences of Being 'Anti-social' in Northern Ireland; Sine;ad Gormally -- 16.Policing the Margins: Anti-Social Behaviour and the 'Underclass Discourse'; Didier Lassalle -- 17. Anti-social Behaviour and the Vulnerable Public; Stuart Waiton -- 18. Anti-Social Behaviour: Marginality, Intolerance and the 'Usual Suspects'; Peter Squires -- 19. The Anti-sociality of Anti-social Behaviour Policy; Emma Bell -- PART III: ANTI-SOCIAL BEHAVIOUR, RECREATION AND LEISURE -- 20. 'Roughs on the Turf' and 'Suburban Saturnalia': Anti-social Behaviour on Victorian Racecourses; Emmanuel Roudaut -- 21. Victorian Respectability, 'Anti-social Behaviour' and the Music Hall, 1880-1900; John Mullen -- 22. Drunkenness, Anti-social Behaviour, Class, Gender and Alcohol in the Making of the Habitual Drunkards Act, 1870-1879; An Vleugels -- 23. Symbolism and the 'Free Market': The Regulation of Alcohol and Anti-social Behaviour Past and Present; Deborah Talbot -- 24. Psychotic (e)states: Where Anti-social Behaviour is Merged with Recreational Drug Use to Signify the Social Problem Group; Shane Blackman and Andrew Wilson -- 25.Regulating Anti-Social Behaviour and Disorder Amongst Football Spectators; Mark James and Geoff Pearson